Collision Mitigation algorithm for tracking of RFID based assets in Defence - C. Hema (European Alliance for Innovation (EAI), 2021)
INTRODUCTION: Asset tracking plays a crucial role in Military warehouses, deploying RFID system will be beneficial. When an RFID reader scans multiple tags in the Military warehouse, the missing tags and redundant tag problem occurs due to the signal interferences. To overcome these issues of missing tags and redundant tags, we proposed Cuckoo Search-based Clustering Protocol (CSCP) followed by linear classifier algorithm.OBJECTIVES: The primary objective of this paper is reducing the collision problems in military warehouse.METHODS: In this paper, we propose Cuckoo Search-based Clustering Protocol (CSCP), where cluster heads deleteduplicate data and sends processed data to the base station, Later the TDMA-based graph colouring technique is implemented to prevent reader collision issues in the RFID network. The Linear Classifier algorithm first separates similar data for classification, which in turn reduces the collision occurrence of missing tags and redundant tags. CONCLUSION: In the RFID deployed military warehouse, cluster head readers are selected, and clusters are created. Readers are scheduled to read information from tags in the cluster using the TDMA-based graph coloring algorithm. The linear classifier algorithm classifies the weapon’s data and filters the redundant weapon’s data in RFID deployed military environment.